FOOD DEMAND IN YOGYAKARTA: SUSENAS 2011 - Widarjono, Agus (KINERJA, 2013)
The impacts of economic and demographic variables on food demand in Yogyakarta are estimated usingthe Almost Ideal Demand System (AIDS). Data from the national social and economic survey of households(SUSENAS) in 2011 are used to accomplish the goal of this study. Food demand consists of cereals, sh,meats, eggs and milk, vegetables, fruits, oil and fats, prepared foods and drinks, other foods and tobaccoproducts. Results show that except for meat and tobacco products, demand elasticities for the rest of foods areinelastic and cereals is the least responsive to price change. All ten studied foods are normal good, but theirincome elasticities are very inelastic.Keyword: Almost Ideal Demand System (AIDS), price and income elasticity, Yogyakarta.